2020
DOI: 10.5137/1019-5149.jtn.30065-20.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deep brain stimulation of the subthalamic nucleus on the postoperative levodopa response: one year follow up

Abstract: AIM: To investigate the effect of preoperative levodopa responsiveness to clinical outcomes in the first postoperative year, and to evaluate the changes in the postoperative levodopa responsiveness in patients undergoing subthalamic nucleus (STN) deep brain stimulation (DBS). MATERIAL and METHODS: Forty-nine Parkinson's Disease (PD) patients undergoing bilateral DBS of the STN were included in this study. Their clinical motor symptoms were assessed preoperatively by UPDRS Part III score in both OFF and ON medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…These leads have been shown to provide a larger therapeutic window (100), with one study reporting a 60% improvement in the MDS-UPDRS III score for the on-STN-DBS condition compared to off-STN-DBS (101). In addition, a more recent study also reported a 60% improvement on the UPDRS-III (102). This 60% improvement while on-STN-DBS observed in more recent studies is consistent with the improvement seen in our study (101,102).…”
Section: Stn-dbs Vs Medicationsupporting
confidence: 93%
See 1 more Smart Citation
“…These leads have been shown to provide a larger therapeutic window (100), with one study reporting a 60% improvement in the MDS-UPDRS III score for the on-STN-DBS condition compared to off-STN-DBS (101). In addition, a more recent study also reported a 60% improvement on the UPDRS-III (102). This 60% improvement while on-STN-DBS observed in more recent studies is consistent with the improvement seen in our study (101,102).…”
Section: Stn-dbs Vs Medicationsupporting
confidence: 93%
“…In addition, a more recent study also reported a 60% improvement on the UPDRS-III (102). This 60% improvement while on-STN-DBS observed in more recent studies is consistent with the improvement seen in our study (101,102). Moreover, recent technological advances in the design of DBS leads and implantable pulse generators have increased flexibility for programming that may have led to the dramatic effect of STN-DBS observed in our study (103).…”
Section: Stn-dbs Vs Medicationsupporting
confidence: 92%